2005
DOI: 10.1021/jo051579s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of New Glucocationic Surfactants:  Model Structures for Marking Cationic Surfactants with Carbohydrates

Abstract: [reaction: see text] In this work, we report the synthesis of a new series of glucocationic surfactants, a class of surfactants we introduced very recently. The preparation of the surfactants is based on the synthesis of the 2-bromoethyl-2,3,4,6-tetra-O-acetyl-beta-D-glucopyranoside, whose preparation was studied in order to improve yields and stereoselectivity of this key intermediate. These glucocationic amphiphiles were prepared and studied as a model of cationic surfactants marked with a carbohydrate moiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 48 publications
(98 reference statements)
6
49
0
1
Order By: Relevance
“…In fact, the formation of these ion pairs is normally favoured when the concentration is increased [18] and should be more evident, if occurring, for monomeric surfactants, since they have a higher cmc. As we [28] and others [18,29] have recently found for gluco-cationic surfactants, several surfactants (in particular those having high hydrophobic character) [30] show a tendency for premicellar aggregation. Compounds 1-4b,c showed a maximum in a Λ vs. C 0.5 plot (as exemplified by 2b, Figure 2, c).…”
Section: Conductivity Plot Shapesupporting
confidence: 62%
See 1 more Smart Citation
“…In fact, the formation of these ion pairs is normally favoured when the concentration is increased [18] and should be more evident, if occurring, for monomeric surfactants, since they have a higher cmc. As we [28] and others [18,29] have recently found for gluco-cationic surfactants, several surfactants (in particular those having high hydrophobic character) [30] show a tendency for premicellar aggregation. Compounds 1-4b,c showed a maximum in a Λ vs. C 0.5 plot (as exemplified by 2b, Figure 2, c).…”
Section: Conductivity Plot Shapesupporting
confidence: 62%
“…[18,26b,28,31] As an example, for 2b (Figure 2, c), this maximum in the Λ vs. C 0.5 plot occured at 0.906 m, while the cmc for this surfactant was nearly twice that value at 1.71 m. The formation of premicellar aggregates [28] was also evidenced by a slight curvature towards the κ axis in the κ vs. C plot in the low concentration range for 2b at approximately 0.16 m (see Figure 2, b). We found a minimum in the Λ vs. C 0.5 plot (Figure 2, c) at 0.149 m, which agrees well with the discontinuity in the κ vs. C plot (0.149 m vs. 0.161 m).…”
Section: Conductivity Plot Shapementioning
confidence: 99%
“…This was shown by Zana [28] in a study on gemini ammonium surfactants. In general this behaviour was recently found mostly for gemini surfactants, since they behave like more hydrophobic compounds [6,25,29]. Besides, studies on the formation of ion pairs in water and alcohols showed that the ion pairs have high tendency to form when the whole molecule hydrophobicity is growing [30,31], i.e.…”
Section: Discontinuity At Low Concentrationmentioning
confidence: 92%
“…For single chain N-dodecylpyridinium surfactants of this series, both chlorides (a) and bromides (b), a larger increase of the hydrophobicity is required to observe premicellar aggregation. This was found to occur for gemini ammonium surfactants [28], gemini pyridinium surfactants [26] and glucocationic surfactants [29].…”
Section: Discontinuity At Low Concentrationmentioning
confidence: 93%
“…This phenomenon has been already reported in the literature. [48,57,58,74,75] Rosen et al tentatively introduced the CMCc/CMCsr atio to describe the extent of the difference of the CMC determined by different methods. [74] Analogously,wereported this parameter in Table 1.…”
Section: Introductionmentioning
confidence: 99%